ESTIMASI BENTUK DASAR SUNGAI BERDASARKAN ANALISA BESAR BUTIR SEDIMEN DI MODIFIED AJKWA DEPOSITION AREA (ModADA) TIMIKA, PAPUA - Budhi Setiawan; Edy Sutriyono; Merri Jayanti (Magister Teknik Geologi Program Pascasarjana UPN ”Veteran” Yogyakarta, 2010)
Tailing is one of waste types produced by mining activity at PT. Freepot Indonesia (PTFI), and it is also called as sirsat, which is the representing abbreviation from sand in mining. The sirsat is placed at ModADA (Modified Ajkwa Deposition Area), an area that has been modified and managed for sirsat deposits. This area is about 235 square kilometres, which is bounded from the surrounding region by West Levee and East Levee. The system used by utilizing the river flow to carry the tailing from the mountain to the deposition area in ModADA.The river flow along the channel contains eroded materials which are correlated with the friction factor, velocity of sedimentation, and geometric configuration showing the bed river morphology. Grain size is a factor influencing the bed river morphology which is used as parameter in this study. The measurement and accumulation of sirsat grains have been conducted since 1997 up to now, and at the same time construction of river cross sections from highland to lowland in ModADA has also been made. These parameters are then utilized for analysis by using statistical approach such as mean, variance, and standard deviation. Estimation of the bed river morphology is carried out by analysing the characteristics of channel base form on the basis of the D50 sediment grain sizes. The estimation of the bed river morphology may be used to predict sedimentation pattern of the river flow in Ajkwa lowland in Timika, Papua.Keywords: ModADA, Grain Size, Bedriver, Sedimentation